The effect of corporate social responsibility recognition on organisational commitment in global freight forwarders - Jiyoung Ko; Hyunmi Jang; Sang Youl Kim (Asian Journal of Shipping and Logistics (AJSL), 2021)
One of the serious inquiries for industry experts and academics is whether and how corporate social responsibility (CSR) can help create better workplace environments. However, this has not been studied enough so far from employees' perspective. To fill this gap, this study aims to examine the relationship between employees' perception on corporate social responsibility (CSR), their job satisfaction, organisational trust and ultimately, organisational commitment to suggest academic and practical implications on sustainable management for international freight forwarders in Korea. For this study, 166 global logistics companies in Busan, one of the world's leading maritime cities, were targeted, and questionnaires were surveyed from 10 April to 30 May 2019. A total of 265 questionnaires were analysed to verify the relevance of individual hypothesis in the research model through confirmatory factor analysis and structural equation model analysis using AMOS 18.0. The results of five hypotheses testing demonstrated a positive and significant effect except that Hypothesis 4 on 'job satisfaction will have a significant effect on organisational commitment' was rejected. Overall, this paper provides important insights into the significance of CSR in global freight forwarding companies with theoretical development and the empirical test of CSR model, highlighting the trust to increase the organisational commitment of employees.
Keywords: 650; Corporate social responsibility; International freight forwarder; Job satisfaction; Korea; Organisational commitment; Organisational trust